Estimation of genetic parameters and prediction of breeding values for some economic traits of Black Bengal Goat under farming condition (Bangladesh Journal of Livestock Research, 2020)
The study was undertaken to evaluate the genetic progress of Black Bengal Goat (BBG) by estimating genetic parameters viz. heritability and breeding values for economically important productive and reproductive traits (birth weight, weight at 3, 6, 9 & 12 months, daily milk yield, lactation length, total milk yield and litter size of BBG goat population). Variance and co-variance components were analyzed applying Residual Maximum Likelihood (REML) approach by VCE 4.2.5 computer package. The heritability (h2) of birth weight was estimated as 0.2, which was low. The heritability estimates for 3-month weight (0.40), 6-month weight (0.50), 9-month weight (0.37) and 12-month weight (0.36) were found medium. Estimated h2 of daily milk yield, total milk yield and lactation length in this study were from 0.55 to 0.82.  h2 of litter size was 0.09. The maximum estimated breeding value (EBV) was found for 6 month body weight (12.94 kg), however, for daily milk yield, the value was 1.513 kg. The results found in this study revealed that genetic improvement of BBG for most of the traits is possible by selection and breeding.Bangladesh J. of Livestock Res. 20(1-2): 8-17, Jan-Dec 2013